Health alterations in nursing students after a year from admission to the undergraduate course - Rodrigo Marques da Silva; Ana Lúcia Siqueira Costa; Fernanda Carneiro Mussi; Victor Cauê Lopes; Karla de Melo Batista; Osmar Pereira dos Santos
ABSTRACT Objective: To identify health alterations in nursing students after a year from admission to a nursing undergraduate course. Method: A longitudinal prospective study with a quantitative approach was carried out in 2016 with first-year nursing students from two universities in the state of São Paulo. The following instruments were applied at the beginning and the end of the first school year: an instrument for Assessment of Stress in Nursing Students, the Center for Epidemiologic Studies Depression Scale, and the Pittsburgh Sleep Quality Index. The ANOVA test for mixed models was used for analysis. Results: The sample was made up of 117 students in March and 100 students in December. A significant increase in stress in all dimensions of the instrument, a reduction in the duration and subjective quality of sleep, and an increase in general stress and depressive symptoms were observed. Conclusion: The nursing academic environment presents the potential for students to become ill. Institutions should rethink their curricular elements, promote resilience, and create spaces to promote students' health.